Timing in initiating lung cancer treatment after bronchoscopy in France: Study from medico-administrative database. (May 2016) - Kudjawu, Yao Cyril; Chatellier, Gilles; Decool, Elsa; de Maria, Florence; Beltzer, Nathalie; Grémy, Isabelle; Meyer, Guy; Eilstein, Daniel
Highlights: We analyzed data from hospital-discharge database. We studied times-to-treatment after bronchoscopy in patients with lung cancer. Times-to-treatment were studied according to the patients pathway and to the treatment combination. We studied time to first treatment according to the residence of the patients. Abstract: Background: Time-to-treatment of cancer is becoming a serious political and social issue. A greater understanding of the timeframes involved in cancer care is needed to reduce inequalities in access to care caused by delays. Objective: To describe time delays in each phase of lung cancer treatment after bronchoscopy. Method: Using the international classification of diseases and medical procedures codes, from national hospital discharge database we selected patients newly diagnosed for Lung cancer in 2009–2010 who had undergone treatment. Results: We included 14, 596 patients. Median times from bronchoscopy to 1) neo-adjuvant chemotherapy and to surgery in patients with surgical pathway were 34d (Q25 = 22; Q75 = 47) and 44d (Q25 = 26; Q75 = 82), respectively, 2) chemotherapy and to radiotherapy in patients with non-surgical pathway, were 33d (Q25 = 22; Q75 = 49) and 88d (Q25 = 46; Q75 = 162) respectively, 3) first treatment irrespective of pathway and treatment combination was 34d (Q25 = 22; Q75 = 50). Time to first treatment was significantly higher with age and with the status of the first care center. It was longer in most northern regions and in overseas districts and shorter in southern and eastern regions of the country. Conclusion: To our knowledge, this is the first study based on medico-administrative database describing time to first treatment after bronchoscopy in patients suffering from lung cancer in France. It could inform decision-making on guidelines on times to access lung cancer treatment.